Nutrient profiling in goats raised by smallholders and institutional farms in Bachok and Pasir Puteh Districts, Kelantan, Peninsular Malaysia - Wan Zahari Mohamed; Al-Khayat D. Ali; Abdul Rahman, A; Muhammad M.S.; Nik Siti Mariani, H (2012)
A study was conducted to investigate the nutrient profiling of growing Boer-crosses goats reared by smallholders in Bachok and Pasir Puteh Districts, Kelantan, Peninsular Malaysia. Daily rations, encompasing about 60% garss and 40% concentrate mixture, were analyzed for proximate and selected minerals (Ca, P, Mg, Na, K and Cu), while blood plasma of the animals were analyzed for minerals only. The results were compared with those managed under the institutional environments in the same locations, where improved feeding and management were practised. The results demonstrated large variations in the content of dry matter (DM), crude fibre (CF), crude protein (CP), ether extract (EE), ash, Ca, P, Mg, Na, K and Cu, both in smallholders and institutional (MARDI) farms. Daily intake of nutrients by the animals under the smallholders condition was estimated below requirement, causing reduced animal performances and body conformation as compared with those under institutional condition. However, the deficiencies and imbalances in the nutrients studied are marginal to induce definite clinical symptoms. In the latter case, improved feeding system can still result in inferior growth performance. Parasite infestation was identified as a factor contributing to this effect. Practical methods to enhancing goat productivity under smallholders environment are highlighted.